Effect of Remineralization Agents on Molar-Incisor Hypomineralization-Affected Incisors: A Randomized Controlled Clinical Trial - KARGÜL, BETÜL (My University, 2022)
Objective: The objective of this study was to evaluate the remineralization effect of two different mineral containing agents on white/creamy and yellow/brown demarcated opacities in incisors in children with molar-incisor hypomineralization (MIH) by using laser fluoresence (LF). Study Design: Fifty-three children (n=401 lesions) with MIH were randomly divided into three groups: (1)calcium glycerophosphate (CaGP), (2)casein phosphopeptide amorphous calcium fluoride phosphate (CPP-ACFP) and, (3)control (1450 ppm fluoride toothpaste). Remineralization was evaluated by means of LF, at baseline, after one and threemonths. Anova Test for Repeated Measurements in intra-group comparisons in evaluating the effectiveness of remineralization agents. One-way Variance Analysis (ANOVA) and Tukey-Kramer Multiple Comparison test were used in the comparisons between groups and, Student Newman Keuls Multpile Comparison Test was used to determine the differences between the measurement averages in case of p<0.05. Results: There was a significant improvement in MIH-lesions over time in all groups (p<0.001), with no differences between groups. The highest percentage of change was observed in CPP-ACFP in lesions LF≤20 scores and the mean percentage of change LF>20 scores, the highest percentage changes in CaGP. There was no significant difference between the groups over the time for all the used outcome measures (p>0.05). Conclusion: The additional use of both mineral containing agents in MIH-affected teeth improved these hypomineralized lesions with mineral deposition. Even if both agents could be used in the hypomineralized teeth with demarcated opacities, future studies are recommended the long-term effect of these mineral containing agents with longer observation and a larger sample size. Keywords: Molar incisor hypomineralization, Calcium glycerophosphate, Casein phosphopeptideamorphous calcium phosphate nanocomplex, Tooth remineralization.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Diş Hekimliği; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; Dentistry; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Klinik Tıp; Klinik Tıp (MED); PEDİATRİ; DENTISTRY, ORAL SURGERY & MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); PEDIATRICS; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; Pediatrics; Pediatrics, Perinatology and Child Health; Molar incisor hypomineralization; Calcium glycerophosphate; Casein phosphopeptide-amorphous calcium phosphate nanocomplex; Tooth remineralization; AMORPHOUS CALCIUM-PHOSPHATE; LOW-FLUORIDE DENTIFRICES; CASEIN PHOSPHOPEPTIDE; GLYCEROPHOSPHATE; DEMINERALIZATION; TEETH; DIAGNOSIS; CHILDREN; CARIES; MIH; Molar incisor hypomineralization; Calcium glycerophosphate; Tooth remineralization